Retinal disorders in northern Brazilian patients treated with chloroquine assessed by multifocal ERG - Raster, M.; Horn, Folkert; Jünemann, Anselm; Rosa, A. A. M.; Souza, G. S.; Gomes, B. D.; Lima, M. G.; Silveira, L. C. L.; Kremers, Jan (Documenta Ophthalmologica, 2011)
The effects of chloroquine intake on the retinal function in a Brazilian population of patients were assessed by multifocal electroretinography. Twenty-four randomly chosen eyes of patients treated with chloroquine for rheumatoid arthritis and systemic lupus erythematosus were examined using multifocal electroretinography (mfERG). Control measurements were acquired from 21 randomly chosen eyes of age-matched healthy subjects. None of the study participants had an inherited retinal disease or a Snellen visual acuity reduced to less than 20/40. In patients and control subjects, cumulative chloroquine dose, total daily dose, duration of treatment, retinal examination, visual field defects, visual acuity, and the mfERG were assessed. The average amplitudes and implicit times of the N1, P1, and P2 components of the mfERGs were measured in the central hexagon (R1) and in five rings (R2-R6). The values measured in patients and normal subjects were compared. The P1 amplitudes in R2 were significantly decreased in the patients. In addition, the amplitudes of N1 and N2 in R1 were significantly smaller in the patients. The implicit times of none of the components were significantly different between patients and controls. The response amplitude was not significantly correlated with cumulative dose and duration of intake. There was no correlation with retinal appearance, visual field, and visual acuity. In agreement with earlier data, the central mfERG amplitudes were decreased in chloroquine patients indicating functional alterations in the retina. These changes are also present in a Brazilian population suggesting that the effects of chloroquine are general and that genetic background and life circumstances probably have, if at all, only little effect.
EVALuna2:21006